PagMYB73A enhances poplar salt tolerance by facilitating adventitious roots elongation and stomata density - Xia Jin; Kai Zhao; Jia Hu; Oliver Gailing; Lieding Zhou; Shuhui Du; Youzhi Han; Shengji Wang (Forestry Research)
MYB transcription factors (TF) are recognized as significant regulators in facilitating plant adaptation to various biotic and abiotic stresses. In order to elucidate the involvement of MYB TFs in the growth, development, and salt tolerance of poplar, PagMYB73A was cloned from 84K poplar (Populus alba × P. glandulosa) and utilized as the target gene for generating PagMYB73A overexpressing transgenic lines (OE-1 , OE-8 , OE-12). Compared to the wild type (WT) plants under normal conditions, the OE lines exhibited enhanced plant height and increased leaf number. While under NaCl treatment, the OE lines displayed elongated adventitious roots but reduced plant height compared to WT. At the transcriptional level, the expression of four genes associated with adventitious root growth and development was examined, revealing higher expression levels in WT compared to OE under normal conditions, but the opposite pattern was observed under salt stress. Physiological index analysis demonstrated a significant decrease in stomatal density of WT under salt stress, whereas the reduction was not significant in OE lines. Furthermore, OE lines exhibited decreased content of malondialdehyde (MDA), a marker of cellular membrane damage, compared to WT under salt stress. In summary, this study preliminarily revealed the regulatory function of PagMYB73A in poplar growth and salt stress resistance, highlighting its active role in the adaptation of poplar to salt stress.